Turkey's Humanitarian Aid Through Education Provision of the Syrian Children School-Aged Refugees - Muttaqien, Audi Izzat; Surwandono, Surwandono (Jurnal Hubungan Internasional, 2023)
The article explains how the Turkish government carries out a policy of providing education for Syrian school-age refugees. Turkey is the largest recipient and the second largest contributor of Syrian refugee aid, primarily as a transit country with many refugees bound for Europe via Turkey before continuing to their destination countries. As the host of refugees, a significant amount requires Turkey to help and facilitate them to access various services, such as social services, health, and especially education for school-age children. The study uses qualitative methods through data collection in literature studies and descriptive data analysis. The study uses qualitative methods through data collection in literature studies and descriptive data analysis. Research has found that Turkey's education policy has shown significant results, helping Syrian refugees at school age because of the ease of access to education that can be obtained, including rights and benefits equal to other Turkish children. Policies imposed by Turkey, such as psychological assistance for children who are still experiencing trauma and the provision of facilities in temporary education or Turkish public schools, have been successfully adopted.